Electrochemical Detection of Hydroquinone Using Yttrium Oxide-Nafion Modified Glassy Carbon Electrodes - Segura-Segura, R; Segura-Segura, R; Penagos-Llanos, J; Penagos-Llanos, J (Elsevier B.V., 2025)
In this article, we report for the first time a novel method for developing modified electrodes using only yttrium oxide and Nafion on glassy carbon (N-YOX/GCE) as well as the application of this method for detecting hydroquinone (HQ). Cyclic voltammetry (CV) and scanning electron microscopy (SEM) were used to characterize the surface and activity of N-YOX/GCE. This simple electrode showed higher selectivity for the electrooxidation of HQ than catechol, with a limit of detection of 1.0 µmol/L under acidic conditions. The utility of the sensor was tested with real samples of human urine and drinking water spiked with hydroquinone. © 2025 The Authors